Prognostic factors in patients with septic disseminated intravascular coagulation treated with thrombomodulin: the effect of reduced thrombomodulin dose; a single-center, retrospective, observational study - Yoshihiro Nishita; Masatoshi Taga; Masaru Sakurai; Yoshitsugu Iinuma; Togen Masauji (BMC, 2022)
Abstract Background Human soluble recombinant thrombomodulin (TM alfa), a treatment for septic Disseminated intravascular coagulation (DIC), is recommended for patients with severe renal dysfunction in reduced doses. However, no studies have examined yet how dose reduction affects clinical efficacy. In this study, we investigated the significance of the TM alfa dose as a prognostic factor in clarifying the clinical background factors related to the clinical effect of TM alfa in patients with septic DIC. Methods This study involved 102 patients with septic DIC admitted to a single-center intensive care unit between April 2013 and March 2020, receiving TM alfa. The following factors were retrospectively collected from the medical records of the target patients: (1) patient background, (2) sequential organ failure assessment (SOFA) score, (3) Japanese Association for Acute Medicine DIC diagnostic criteria score, (4) DIC treatment information, (5) TM alfa dose per bodyweight (normal dose: 0.06 mg/kg or reduced dose: 0.02 mg/kg), (6) DIC resolution within 7 days after the start of TM alfa administration (DIC resolution), (7) all deaths within 30 days after the start of TM alfa administration (30-days-all-cause mortality), (8) presence or absence of new hemorrhagic side effects after the start of TM alfa administration. Multiple logistic regression analysis was used to assess factors associated with DIC resolution and 30-days-all-cause mortality. Results The SOFA score (odds ratio: 95% confidence interval, 0.76: 0.66-0.89), pneumonia (0.24: 0.08-0.75), and reduced dose administration of TM alfa (0.23: 0.08-0.66) were independent of and negatively related to the DIC resolution. For the 30-days-all-cause mortality, the SOFA score (1.66: 1.31-2.09), pneumonia (9.50: 2.49-36.25), and TM alfa dose reduction (3.52: 1.06-11.69) were independent, poor prognostic factors. We found no association between the hemorrhagic side effects and the TM alfa dose per bodyweight. Conclusions The reduced dose of TM alfa for patients with severe renal dysfunction was observed to be an influential factor for DIC resolution and 30-day all-cause mortality, as were SOFA scores and pneumonia. Further studies are required in the future to verify this finding.